MANAJEMEN KEUANGAN DAN PENGGALIAN SUMBER DANA DI LEMBAGA PENDIDIKAN - NURAINI (CV. ADIBA AISHA AMIRA, 2026)
Educational financial management involves the transparent and efficient planning, organising, managing and accounting for funds (RAPBS) to improve the quality of education. Fundraising involves optimising sources from the government (BOS), parents or the community (committees), foundations, and school business units, in order to meet the operational and development needs of educational institutions, namely schools. “Education funding is a shared responsibility between the Government, Local Governments, and the community”. Furthermore, Article 2, paragraphs (1) and (2) of Government Regulation No. 48 of 2008 on Education Funding state that education funding is a shared responsibility between the central government, local governments, and the community. The community referred to includes: educational institutions established by the community; students, parents or guardians of students; and other parties besides those mentioned who have an interest and role in the field of education. Development funding, which includes long-term investments to improve the quality of education, such as teacher training, curriculum development, and the construction of learning facilities. 3. Contingency funding, which is allocated for urgent needs or extraordinary events that cannot be planned in advance.